C18:0 GM3 ganglioside’s efficacy in LPS-induced parkinsonism: neuroprotection, inflammatory inhibition and gliosis mitigation - Tsung-Ta Liu; Cheng-Tsung Liu; I-Hsun Li; Yu-Chieh Chu; Hao-Yuan Hung; Chuang-Hsin Chiu; Ta-Kai Chou; Shiao-Yun Li; Tin-An Wang; Jui-Hu Shih (Behavioral and Brain Functions)
Abstract Background Parkinson’s disease (PD) is an incurable neurological disorder, and current pharmacological therapies primarily address symptoms without halting disease progression. Emerging evidence highlights PD as a neuroinflammatory disease, with chronic brain inflammation preceding the onset of motor dysfunction. This study investigates the role of C18:0 GM3, a long-chain fatty acids-containing ganglioside, in modulating inflammatory responses in PD, exploring its therapeutic potential in mitigating LPS-induced parkinsonism. Methods Male C57BL/6 mice were utilized in an LPS-induced PD model to evaluate the neuroprotective effects of C18:0 GM3 ganglioside. Pre-treatment with C18:0 GM3 was assessed through behavioral tests, including rotarod and beam-walking, to determine motor function improvements. Dopaminergic neurotoxicity was quantified using [18F]FE-PE2I positron emission tomography (PET) imaging and tyrosine hydroxylase (TH) staining. The anti-inflammatory and anti-gliosis effects of C18:0 GM3 were analyzed by measuring cytokine levels (IL-1β, TNF-α) and by assessing Iba1 and GFAP immunoreactivity as indicators of microglial and astrocytic changes, respectively. Results Pre-treatment with C18:0 GM3 ganglioside significantly enhanced motor coordination and balance, as evidenced by improved performance in rotarod and beam-walking tests. Furthermore, C18:0 GM3 ganglioside effectively attenuated LPS-induced dopaminergic neurotoxicity, evidenced by increased striatal dopamine transporter availability on [18F]FE-PE2I PET imaging and the preservation of TH-positive neurons in the striatum. In addition, C18:0 GM3 markedly suppressed the expression of pro-inflammatory cytokines, including IL-1β and TNF-α, along with cyclooxygenase-2 levels. C18:0 GM3 also reduced gliosis, as demonstrated by a decrease in Iba1-positive microglial cells and GFAP-positive astrocytes. Conclusion Our data indicate that C18:0 GM3 primarily attenuates the TLR4-driven inflammatory cascade initiated by intrastriatal LPS, thereby secondarily preserving striatal dopaminergic terminals and improving motor deficits. Although these results highlight anti-inflammatory neuroprotection, additional studies are required to determine whether GM3 also modulates downstream Parkinson-specific processes such as α-synuclein aggregation or progressive neurodegeneration.